Towards primary care for non-serious 999 callers: results of a controlled study of "Treat and Refer" protocols for ambulance crews. Issue 6 (2nd December 2004) - Snooks, H; Kearsley, N; Dale, J; Halter, M; Redhead, J; Cheung, W Y
Abstract : Objective: To develop and evaluate "Treat and Refer" protocols for ambulance crews, allowing them to leave patients at the scene with onward referral or self-care advice as appropriate. Methods: Crew members from one ambulance station were trained to use the treatment protocols. Processes and outcomes of care for patients attended by trained crews were compared with similar patients attended by crews from a neighbouring station. Pre-hospital records were collected for all patients. Records of any emergency department and primary care contacts during the 14 days following the call were collected for non-conveyed patients who were also followed up by postal questionnaire. Results: Twenty three protocols were developed which were expected to cover over 75% of patients left at the scene by the attending crew. There were 251 patients in the intervention arm and 537 in the control arm. The two groups were similar in terms of age, sex and condition category but intervention cases were more likely to have been attended during daytime hours than at night. There was no difference in the proportion of patients left at the scene in the intervention and control arms; the median job cycle time was longer for intervention group patients. Protocols were reported as having been used in 101 patients (40.2%) in the intervention group; 17 of the protocols were recorded as having been used at least once during the study. Clinical documentation was generally higher in the intervention group, although a similar proportion of patients in both groups had no clinical assessments recorded. 288 patients were left at the scene (93 in the intervention group, 195 in the control group). After excluding those who refused to travel, there were three non-conveyed patients in each group who were admitted to hospital within 14 days of the call who were judged to have been left at home inappropriately. A higher proportion of patients in the intervention arm reported satisfaction with the service and advice provided. Conclusions: "Treat and Refer" protocols did not increase the number of patients left at home but were used by crews and were acceptable to patients. The protocols increased job cycle time and some safety issues were identified. Their introduction is complex, and the extent to which the content of the protocols, decision support and training can be refined needs further study.